THE SOURCE OF GRANITIC GNEISSES AND MIGMATITES IN THE ANTARCTIC PENINSULA: A COMBINED U–PB SHRIMP AND LASER ABLATION HF ISOTOPE STUDY OF COMPLEX ZIRCONS - Flowerdew M.J.; Millar I.L.; Vaughan A.P.M.; Horstwood M.S.A.; Fanning C.M. (My University, 2006)
Zircons gneisses and migmatites collected from the Antarctic Peninsula have different core–rim hafnium isotope ratio relationships depending on whether evidence for zircon dissolution is present or absent. Two samples contain inherited zircon that is partially dissolved. In these samples, the 176Hf/177Hf rations of the inherited zircon and new magmatic zircon rims are, on average, indistinguishable and consistent with in situ melting. In such cases the hafnium isotopic composition of the melt was probably strongly influenced by the dissolved zircon component at the source. Variation in 176Hf/177Hf within the magmatic zircon rims from grain to grain suggests that Hf isotopes were only partially homogenized during melt migration; alternatively, zircon growth may have taken place within small volumes of partial melt. Other samples do not preserve textural evidence for zircon dissolution during melt generation; in these samples the 176Hf/177Hf values of the inherited zircon and new magmatic zircon rims are different. The zircon rims apparently suggest a source of less evolved hafnium than that contained within the inherited zircon. Whether this relates to a separate juvenile source or, alternatively, is derived from minerals other than zircon at the source, cannot be resolved. Inherited zircon, irrespective of age, has been strongly influenced by the reworking of a juvenile Late Mesoproterozoic source, suggesting that such crust underlies the Antarctic Peninsula. Our results therefore suggest that Hf isotope analyses provide great potential for future studies investigating the source and processes involved in the generation of crustal melts.
Keywords: ZIRCON; ANTARCTIC PENINSULA; DETRITAL ZIRCON; ISOCHRON; PENINSULA GNEISS; Докембрий::Протерозой::Мезопротерозойская; Precambrian::Proterozoic::Mesoproterozoic